Remarks on Heyting algebras with tense operators - Figallo, Aldo Victorio (2012)
The concept of tense operators on Heyting algebras was introduced in [3]. The aim of this paper is to prove, that the set of axioms proposed by I. Chajda in [3, Deﬁnition 1], is a dependent axioms system and show that tense operators F and P can not be regarded as existential quantiﬁers.